A case series of multiple meningiomas with different histology - Shilpi Banga; Hiba Salam; Manpreet Singh Banga; Sandeep BV; Raj Swaroop Lavadi (Asian Journal of Medical Sciences, 2023)
Multiple meningiomas (MMs) tend to be benign with uniform histology. It is uncommon to find sporadic MMs having different histological features in the same patient. In this case series, of the four patients diagnosed with MM, two patients had different histopathology. An updated review of literature was then performed, providing the different histopathology in those cases. The first case was unique as the patient had an intradiploic meningioma with an intraparenchymal meningioma. Histology found in these cases represented WHO Grade I meningioma. After performing a literature search, it is likely that these tumors do not arise from clonal expansion, but rather have an independent origin.